Are alternative livelihood projects effective at reducing local threats to specified elements of biodiversity and/or improving or maintaining the conservation status of those elements?. Issue 1 (December 2015) - Roe, Dilys; Booker, Francesca; Day, Mike; Zhou, Wen; Allebone-Webb, Sophie; Hill, Nicholas; Kumpel, Noelle; Petrokofsky, Gillian; Redford, Kent; Russell, Diane; Shepherd, Gill; Wright, Juliet; et al.
Abstract Background Alternative livelihood projects are used by a variety of organisations as a tool for achieving biodiversity conservation. However, despite characterising many conservation approaches, very little is known about what impacts (if any) alternative livelihood projects have had on biodiversity conservation, as well as what determines the relative success or failure of these interventions. Reflecting this concern, Motion 145 was passed at the Vth IUCN World Conservation Congress in 2012 calling for a critical review of alternative livelihood projects and their contribution to biodiversity conservation. This systematic map and review intends to contribute to this critical review and provide an overview for researchers, policy makers and practitioners of the current state of the evidence base. Methods Following an a priori protocol, systematic searches for relevant studies were conducted using the bibliographic databases AGRICOLA, AGRIS, CAB Abstracts, Scopus, and Web of Knowledge, as well as internet searches of Google, Google Scholar, and subject specific and institutional websites. In addition, a call for literature was issued among relevant research networks. The titles, abstracts and full texts of the captured studies were assessed using inclusion criteria for the systematic map and the systematic review, respectively. An Excel spreadsheet was used to record data from each study and to provide a systematic map of the evidence for the effectiveness of alternative livelihood studies. The studies that met additional criteria to be included in the systematic review were described in more detail through a narrative synthesis. Results Following full text screening, 97 studies were included in the systematic map covering 106 projects using alternative livelihood interventions. Just 22 of these projects met our additional criteria for inclusion in the systematic review, but one project was removed from the detailed narrative synthesis following critical appraisal. The 21 included projects included reports of positive, neutral and negative conservation outcomes. Conclusions Our results show that there has been an extensive investment in alternative livelihood projects, yet the structure and results of most of these projects have not been documented in a way that they can be captured using standardised search processes. Either this is because there has been little reporting on the outcomes of these projects, or that post-project monitoring is largely absent. The implications of this review for policy, management and future research are provided in relation to this evidence gap.